How Feminist knowledge affects attitude towards brand femvertising: The mediating effects of authenticity and credibility - Atziri Martínez-Aguirre; Judith Cavazos-Arroyo; María Victoria Carrillo-Durán (Social Sciences and Humanities Open)
Femvertising, an acronym for “feminism” and “advertising”, means a change in the traditional representation of women in advertising campaigns, incorporating messages of empowerment and promoting gender equality. This study has two objectives: first, to analyze the effect of consumers' knowledge about feminism, the authenticity, credibility, and attitude towards femvertising of the brand, and the influence of the latter on the eWOM of femvertising and WOM of the brand. Second, to analyze the mediating effects between feminist knowledge and attitude towards brand femvertising. A quantitative, explanatory, and cross-transversal study was conducted with 407 women who reported being familiar with the Avon® brand in Mexico. The results of the structural equation model indicate that knowledge positively influences the perception of authenticity, credibility, and attitude. In turn, attitude is positively affected by both knowledge and credibility but not by authenticity. Similarly, attitude has a positive impact on eWOM and WOM. Finally, the findings reveal that the perceived authenticity of femvertising does not mediate the relationship between feminist knowledge and attitudes toward a brand's femvertising, whereas credibility exerts a partial mediation between these constructs. This study contributes to both advertising literature and professional marketing practice by providing a deeper understanding of underexplored concepts within femvertising, particularly the role of feminist knowledge and its impact on a brand's authenticity, credibility, consumer attitudes, WOM, and eWOM.